Implementation of Quality Academic Guidance Services Based on Lokal Wisdom (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to determine the application of batak cultural values in improving mutu academic guidance services. To get a good quality of service can be achieved through a cultural values approach. The cultural values that will be used in this study are cultural values that exist in the Batak community. This research uses qualitative research methods with the type of case study research. Data collection techniques through interviews, Documentation Observation and Focus Group Discussion (FGD). Research Results by applying the value of local wisdom: 1. Marnonang, marsirarian, marpollung, in academic guidance activities such as Study Together, Off campuses Assignment, Joint Scientific Meetings, 2. Pantun Hangoluan, Tois Hamagoan in academic guidance through Sport and fun games, Campus Clean Up, Prayer in Turn, 3. Marsiamin aminan songon lambok ni Gaol marsitungkol tungkolan songon suhat in Roberan through Social fun activities, Do Smart to Manage Out Trash, Community Servic.The implementation of the quality of academic guidance services based on local wisdom is very good and effectively carried out so that students are more socially sensitive and pay attention to the cultural values that prevail in the surrounding environment and make students wiser in adapting.